Analisis Yuridis Penyidikan Narkoba Menyesuaikan Pasal 114 No 112 Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika di Polres Kota Mojokerto - Zakky Maulana Afizuddin; Nur Handayati; M. Syahrul Borman (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to analyze the investigation of narcotics crimes conducted by the Mojokerto City Police in accordance with the provisions of Article 114 in conjunction with Article 112 of Law Number 35 of 2009 concerning Narcotics. These articles regulate the threat of criminal penalties for drug dealers and users, and provide a legal basis for law enforcement officers in carrying out the investigation process. This study uses a normative legal method with a statutory approach and case analysis. The results of the study indicate that the investigation at the Mojokerto City Police has attempted to comply with applicable legal provisions, but there are obstacles such as a lack of competent human resources, obstacles in collecting evidence, and challenges in implementing rehabilitation for drug users. This study recommends increasing the capacity of investigators through training, optimizing cooperation with related agencies, and implementing more transparent and accountable investigation procedures.